Large eddy simulation and experimental study of turbulent mixed convection inside a cavity with large Rayleigh number: Effect of buoyancy. (15th March 2019) - Huang, Y.Y.; Yang, G.; Wu, J.Y.
Abstract: Turbulent mixed convection characteristics inside a rectangular cavity are studied experimentally and numerically. Hot wire anemometry (HWA), particle image velocimetry (PIV) and thermocouples were used to study the velocity and temperature field for Re = 8.3 × 10 3 and Ra = 4.34 × 10 12 . The Large Eddy Simulation (LES) was carried out using the dynamic Smagorinsky model and the Favre-averaging method for 1.08 × 10 12 ≤ Ra ≤ 6.50 × 10 12 to further investigate the effect of the buoyancy. The time-averaged field demonstrates the circulation flow structure and thermal stratification in the cavity. The heat transfer on the heated side wall shows a significant deviation from natural convection due to the center jet flow. The turbulent flow development and coherent structures induced by buoyancy and shear force are presented with the second invariant of the velocity gradient tensor. The turbulence quantities such as velocity and temperature fluctuation, and turbulent heat flux are found highly concentrated near the heated side walls and the center jet boundary, and increase significantly with buoyancy. By comparing the experimental results, the accuracy of the LES for mixed convection is also determined. Highlights: The mean flow field is occupied with a large scale circulation structure. Turbulence quantities are concentrated near the heated wall and the jet boundary. Turbulence quantities increase with the buoyancy and become more concentrated. LES shows a good consistency in mean velocity and temperature field. The lateral distribution of turbulence quantities by LES agree with experiment.